If you begin with the basic equation of a vertical parabola: y-k=a(x-h)^2, where (h,k) is the vertex, then that equation, when the vertex is (-3,-2), is
y + 2 = a (x + 3)^2. If we solve this for y, we get
y = a(x+3)^2 - 2. Thus, eliminate answers A and D. That leaves B, since B correctly shows (x+3)^2.
Answer:
54.6
Step-by-step explanation:
42 = 70%
100% - 70% = .30%
42 x 1.3 = 54.6
Answer:
A. 7 years old
Step-by-step explanation:
6x-7=35 is the equation.
Add 7 to both sides, which gives you 6x=42.
Then both sides by 6, so 6/6=x and 42/6=7
So, x=7.
Since x is his daughter's age, x=7, so his daughter is 7.
Answer:
3 and 6
Step-by-step explanation: